Modeling and Simulation of an Unpowered Lower Extremity Exoskeleton Based on Gait Energy. (10th August 2020) - Wang, Yongfeng; Kong, Xiangzhan; Yang, Jing; Li, Guanglin; Zhao, Guoru
Abstract : Aiming at the problem of how to store/release gait energy with high efficiency for the conventional unpowered lower extremity exoskeletons, an unpowered lower-limb exoskeleton is proposed. In the current study, the human motion model is established, and the change rule and recovery/utilization mechanism of gait energy are illustrated. The stiffness and metabolic cost of relevant muscles in lower extremity joints are obtained based on OpenSim software. The results show that stiffness of muscle is increased when muscle concentric contraction generates positive work, but it is reverse when muscle eccentric contraction generates negative work. Besides, metabolic cost of the soleus, gastrocnemius, and tibialis anterior decreased about 31.5%, 34.7%, and 40%, respectively. Metabolic cost of the rectus femoris, tensor fascia lata, and sartorius decreased about 36.3%, 7%, and 5%, respectively, and the total metabolic cost of body decreased about 15.5%, under the exoskeleton conditions. The results of this study can provide a theoretical basis for the optimal design of unpowered lower extremity exoskeleton.